Pengaruh Firm Size, DPR, Financial Laverage, dan Financial Risk terhadap Income Smoothing pada Perusahaan Manufaktur di BEI tahun 2017-2019 - Ni Made Titin Eliawati (UNHI Press, 2022)
A company will definitely seek various ways to improve company performance. This is done so that the company, especially the management, has a positive value in the eyes of investors. The pressure to always show positive performance to management actually has an impact on income smoothing which is carried out when the company's work does not meet expectations. This study aims to determine the effect of firm size, dividend payout ratio, finance al leverage, and financial risk on income smoothing. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period, namely 182 companies with 45 companies as samples. The data collected is secondary data through reports on the IDX with logistic regression analysis. The results of this study illustrate that firm size and financial leverage have a positive effect on income smoothing. Dividend payout ratio and financial risk have no effect on income smoothing.